Late profound muscle weakness following heart transplantation due to danon disease. Issue 1 (21st November 2012) - Van Der Starre, Pieter; Deuse, Tobias; Pritts, Chad; Brun, Carlos; Vogel, Hannes; Oyer, Philip
Abstract Introduction: Postoperative muscle weakness is a serious complication in surgical intensive care patients. It is mostly described as critical illness polyneuromyopathy. Risk factors include intensive care length of stay, sepsis, poor glycemic control, and combined use of corticosteroids and neuromuscular blocking agents, malnutrition, and electrolyte imbalance. Methods: We report a case of late‐progressive, profound weakness after heart transplantation for noncompaction cardiomyopathy which required prolonged mechanical ventilation. The patient's muscle strength recovered completely after prolonged rehabilitation. Results: Electromyographic assessment showed myopathy. Muscle biopsy revealed Danon disease, a genetic disorder affecting the lysosomal‐associated membrane protein 2 gene (LAMP2). Conclusions: The finding of this genetic disorder was unexpected, because the preoperative echocardiographic diagnosis of noncompaction cardiomyopathy has not been reported in Danon disease. This report underlines the need for early availability of pathology results from the explanted heart, which showed the same disorder. Muscle Nerve, 2013